Bringing Purported Black Sheep into the Fold: Galician Inflected Infinitives and Puerto Rican Spanish Pre-Verbal Infinitival Subject Pronouns - Esther Brown; Javier Rivas (Languages, 2019)
This work reports the results of quantitative, variationist analyses of two typologically unusual constructions in order to explore the grammatical conditioning of subject expression in non-finite clauses. Both constructions, Galician inflected infinitives and (Puerto Rican) Spanish preposed, nominative infinitival subjects, have not been widely studied. As a result, variable expression/omission of subject marking in these constructions is not yet fully understood. Using corpora of oral data, we extract 732 examples of infinitives in purpose clauses (headed by para) and employ a logistic mixed effect model to explore the linguistic conditioning of the overt/null variants. We find the appearance of overt subject marking to be conditioned nearly identically across the two distinct languages as well as across finite/non-finite clauses. We utilize this lack of difference to propose that the two construction types may be manifestations of one grammaticalization process. As such, we propose the Puerto Rican Spanish variation may provide a new synchronic source of data with which to explore the diachronic source of (Galician) inflected infinitives.